What Role Can Avatars Play in e-Mental Health Interventions? Exploring New Models of Client–Therapist Interaction - Rehm, Imogen C.; Foenander, Emily; Wallace, Klaire; Abbott, Jo-Anne M.; Kyrios, Michael; Thomas, Neil (Frontiers in Psychiatry, 2016)
In the burgeoning field of e-mental health interventions, avatars are increasingly being utilized to facilitate online communication between clients and therapists, and among peers. Avatars are digital self-representations, which enable individuals to interact with each other in computer-based virtual environments. In this narrative review, we examine the psychotherapeutic applications of avatars that have been investigated and trialed to date. Five key applications were identified (1) in the formation of online peer support communities; (2) replicating traditional modes of psychotherapy by using avatars as a vehicle to communicate within a wholly virtual environment; (3) using avatar technology to facilitate or augment face-to-face treatment; (4) as part of serious games; and (5) communication with an autonomous virtual therapist. Across these applications, avatars appeared to serve several functions conducive to treatment engagement by (1) facilitating the development of a virtual therapeutic alliance; (2) reducing communication barriers; (3) promoting treatment-seeking through anonymity; (4) promoting expression and exploration of client identity; and (5) enabling therapists to control and manipulate treatment stimuli. Further research into the feasibility and ethical implementation of avatar-based psychotherapies is required.